STRATEGY FORMULATION TO NAVIGATE REVENUE FLUCTUATION DURING THE DEATH VALLEY PHASE: A CASE STUDY OF BUNGKUST – A PACKAGING COMPANY - Mulia Arta Kusuma; Harimukti Wandebori (RADJA PUBLIKA, 2026)
This study formulates strategies to reduce revenue fluctuation at Bungkust, a business-to-business custom paper packaging company navigating the Death Valley phase. A single-case study combined semi-structured interviews with employees, customers, and a vendor with internal revenue and marketing-funnel records from January 2025 to May 2026. Interview data were examined through thematic analysis, revenue through descriptive time-series analysis, and funnel records through descriptive statistics. Monthly revenue ranged from IDR 50.14 million to IDR 715.30 million, with major increases repeatedly followed by sharp declines. High traffic did not consistently produce qualified prospects, while only 6-19% of released quotations became orders. The company shows strong growth ambition but lacks a sufficiently standardized and scalable business model, placing it in the Start-up phase of the Death Valley framework. Market, external, and internal analyses generated 23 TOWS alternatives, consolidated into nine strategies. Integrated Cost Leadership/Differentiation was selected to combine cost efficiency with customization, quality, responsiveness, and fulfilment reliability. A preparation phase from Q3 2026 to Q2 2027 and an execution phase from Q3 2027 provide a structured route toward more stable and scalable growth.